Association between smoking and cognitive impairment in multiple sclerosis - Özcan ME (Dove Medical Press, 2014)
Muhammed Emin Özcan,1 Bahri İnce,2 Ayhan Bingöl,3 Simge Ertürk,3 Meriç Adil Altınöz,4 Hasan Hüseyin Karadeli,1 Abdulkadir Koçer,5 Talip Asil1 1Deparment of Neurology, Medical Faculty, Bezmialem Vakif University, Istanbul, Turkey; 2Department of Psychiatry, Bakirköy Research and Training Hospital for Psychiatry, Istanbul, Turkey; 3Mayis Psychology Center, Istanbul, Turkey; 4Department of Molecular Biology and Genetics, Haliç University, Istanbul, Turkey; 5Department of Neurology, Medical Faculty, İstanbul Medeniyet University, Göztepe, Istanbul, Turkey Purpose: Although smoking is known to cause various symptoms in multiple sclerosis (MS) patients, there have been no reports regarding the relationship between smoking and cognitive impairment in MS. Studying the effects of cigarette smoking in MS patients is imperative as there is a high prevalence of cognitive impairment in MS patients. In this study we examined the potentially deleterious effects of heavy smoking on mentation of patients with MS. Patients and methods: MS patients receiving care at the Neurology Clinic at Bezmialem Vakif University, between the ages of 18–65 years who have at least graduated elementary school were included in the study. The Brief Repeatable Battery of Neuropsychological Tests (BRB-N) is a commonly used method to assess cognitive function in MS patients and was utilized in our study. Patients that smoked for at least 10 pack-years were considered heavy smokers.Results: All the patients were stratified into two groups: heavy smokers (n=20) and nonsmokers (n=24). For heavy smokers, their cognitive functioning was more impaired than that of nonsmokers (P=0.04, χ2=4.227). For patients with cognitive impairment, 78.9% of the Paced Auditory Serial Addition Test and 63.2% of the Symbol Digit Modalities Test scores were found to be lower.Conclusion: Previous reports have suggested that smoking increases the frequency of relapse among individuals with relapsing-remitting MS and accelerates disease progression in patients with progressive MS. According to the results of our study, heavy smokers had increased cognitive impairment when compared to nonsmokers. Extensive studies are necessary to further elucidate the relationship between smoking and cognitive impairment in MS patients. Keywords: cigarette, BRB-N, nicotine, cognition, tobacco, mentation, memory